Juridical Review Of The Dissolution Of Marriage For Buddhists In Indonesia (Decision Study No. 66 / Rev.G./ 2024 / PN Mdn) - Safnul, Dody; Azmi, Syariful; Halimatusdiyah, Halimatusdiyah (Legalpreneur Journal, 2025)
Marriage in Buddhism aims to create a happy family, so for that the faithful must follow the teachings of the Buddha about the practice of the right life. The formulation of the problem is how the legal arrangements relating to the dissolution of marriage due to divorce of Buddhists, how the legal consequences of the dissolution of marriage of Buddhism. The research method used is descriptive analysis that leads to normative juridical law research, namely research conducted by referring to legal norms, namely researching library materials or secondary materials. Secondary Data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results showed that in the case of divorce, the Buddhists follow the law of the Republic of Indonesia No. 1 of 1974 on marriage. Article 38 of Law No. 1 of 1974 states that a marriage can be dissolved by death, divorce, or by a court decision. As a result of the divorce law on the position, rights and obligations of the former husband/wife according to Article 41 letter c of Law No. 1 of 1974 is that the court may require the former husband to provide living expenses and/or determine an obligation for the former wife. Normative provisions in Article 41 letter c of Law No. 1 of 1974 are related to Article 11 of Law No. 1 of 1974 which contains normative provisions that a woman who breaks up her marriage applies a waiting period, which then this article has been spelled out in Article 39 of Government Regulation No. 9 of 1975 which contains imperative provisions that for a widow, so the waiting time for widows who are still menstruating is set 3 (three times) holy with at least 90 (ninety) days and for those who are not menstruating set 90 (ninety) days. If the marriage is broken, and the widow is pregnant, the waiting period is set until she gives birth.